2021
DOI: 10.1111/trf.16402
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid desaturase activity in mature red blood cells and implications for blood storage quality

Abstract: BackgroundIncreases in the red blood cell (RBC) degree of fatty acid desaturation are reported in response to exercise, aging, or diseases associated with systemic oxidant stress. However, no studies have focused on the presence and activity of fatty acid desaturases (FADS) in the mature RBC.Study design and methodsSteady state metabolomics and isotope‐labeled tracing experiments, immunofluorescence approaches, and pharmacological interventions were used to determine the degree of fatty acid unsaturation, FADS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 62 publications
(88 reference statements)
4
31
2
Order By: Relevance
“…These results contrast with previous research that has shown an increase in odd-numbered LCFA, but with the exception of GLA, support studies which assert no change in long-chain poly unsaturated fatty acids (LCPUFA) in the PA erythrocytes [14,43,44]. On the other hand, our results are interesting in that they follow opposite trends to those reported recently in the context of storage and the oxidant stress-induced activation of fatty acid desaturases, suggesting that in the absence of additional stressors, RBCs from PA patients are capable of withstanding oxidant stress through the basal activation of other redox pathways (e.g., the PPP) [45]. Since the rate-limiting enzyme of the PPP is glucose 6-phosphate dehydrogenase, which is coded by a gene on chromosome X, it is interesting to speculate whether G6PD dosage might impact the severity of PA in a sex-dependent fashion, with RBCs from females predicted to be better protected from oxidant stress than males carrying the PCC deficiency [22,46].…”
Section: Discussioncontrasting
confidence: 70%
“…These results contrast with previous research that has shown an increase in odd-numbered LCFA, but with the exception of GLA, support studies which assert no change in long-chain poly unsaturated fatty acids (LCPUFA) in the PA erythrocytes [14,43,44]. On the other hand, our results are interesting in that they follow opposite trends to those reported recently in the context of storage and the oxidant stress-induced activation of fatty acid desaturases, suggesting that in the absence of additional stressors, RBCs from PA patients are capable of withstanding oxidant stress through the basal activation of other redox pathways (e.g., the PPP) [45]. Since the rate-limiting enzyme of the PPP is glucose 6-phosphate dehydrogenase, which is coded by a gene on chromosome X, it is interesting to speculate whether G6PD dosage might impact the severity of PA in a sex-dependent fashion, with RBCs from females predicted to be better protected from oxidant stress than males carrying the PCC deficiency [22,46].…”
Section: Discussioncontrasting
confidence: 70%
“…While dysregulation of iron metabolism has been previously associated with increased propensity for lipid stress in stored RBCs or under pathological conditions (e.g., sickle cell disease or thalassemia) (Howie et al, 2019;Buehler et al, 2021), to the best of our knowledge no study has been published correlating intraand extra-cellular levels of iron to the intra-and extracellular RBC metabolome. In our study, iron levels correlated positively with markers of increased oxidant stress in aging RBCs-such as hypoxanthine (Nemkov et al, 2018b) and increased levels of poly-unsaturated fatty acids (consistent with activation of fatty acid desaturases) (Thomas et al, 2021). The former observation is relevant in that RBC-specific AMPD3, the rate-limiting enzyme of AMP deamination upstream to hypoxanthine synthesis-is positively regulated by intracellular calcium levels and oxidant stress (Nemkov et al, 2018b).…”
Section: Discussionsupporting
confidence: 65%
“…of oxidant stress and pyruvate/lactate ratios, perhaps as a result of residual fatty acid desaturase activity in the mature RBC or moonlighting function of other enzymes sensitive to NADH/ NAD + ratios [49].…”
Section: Plos Onementioning
confidence: 99%